The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/adhm.202302305
|View full text |Cite
|
Sign up to set email alerts
|

A Dose‐Dependent Spatiotemporal Response of Angiogenesis Elicited by Zn Biodegradation during the Initial Stage of Bone Regeneration

Junlong Tan,
Shuang Li,
Chaoyang Sun
et al.

Abstract: The indispensable role of zinc (Zn) in bone metabolism endows biodegradable Zn‐based materials with the bioactivity to facilitate bone regeneration in bone trauma. However, the impact of Zn biodegradation on the progress of bone repair remains to be unfolded, especially the angiogenesis, which plays a vital role in the subsequent bone regeneration. It is found that a consistent dose‐dependent spatiotemporal response of angiogenesis is induced by Zn biodegradation both in vivo and in vitro. In a critical bone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
(80 reference statements)
1
6
0
Order By: Relevance
“…As an essential trace element, Zn is involved in many metabolic reactions 25 . In particular, Zn has a regulatory effect on the bone immune system 26,27 inhibit polarization towards pro-inflammatory phenotype macrophage (M1) 28 . Meanwhile, Li demonstrates bone immunomodulatory prowess by enhancing anti-inflammatory factors like Arg1, Il-4, and Il-10.…”
Section: Discussionmentioning
confidence: 99%
“…As an essential trace element, Zn is involved in many metabolic reactions 25 . In particular, Zn has a regulatory effect on the bone immune system 26,27 inhibit polarization towards pro-inflammatory phenotype macrophage (M1) 28 . Meanwhile, Li demonstrates bone immunomodulatory prowess by enhancing anti-inflammatory factors like Arg1, Il-4, and Il-10.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al demonstrated that a pure Zn membrane (30 μm thick) lost less than 30% in thickness and preserved its barrier function after 10 weeks of degradation in a rat calvarial critical-sized bone defect model . Tan et al reported that a compact corrosion product layer was left after complete degradation of the pure Zn foil, which could act as a secondary phase to the barrier functionality of the membrane and provide a barrier effect for a longer period. , Moreover, Si et al fabricated Ca–P-coated Mg-2.0Zn-1.0Gd (wt %) alloys with a degradation rate of 260 μm/yr, and the in vivo results indicated that the alloy can fulfill its task without rupture for 3 months . In this study, the Mg/Cu-MOF-coated samples presented a suitable degradation rate of 65.0–146.1 μm/yr.…”
Section: Resultsmentioning
confidence: 99%
“…2a, the composite hydrogels of Zn 2+ @TA and Fe 2+ -Zn 2+ @TA gave relatively greater OD values than Fe 2+ @TA and pure H, probably because Zn 2+ could enhance cell proliferation. 30,31 In particular, upon NIR irradiation (10 min, 808 nm, 1 W cm −2 ), H-Fe 2+ -Zn 2+ -NIR and H-Fe 2+ -NIR achieved a higher OD than those without NIR irradiation, showcasing mild photothermal stimulation on cell proliferation. 11 Moreover, the hydrogel dressing would directly contact damaged tissues, and the blood compatibility was characterized by an in vitro hemolysis experiment.…”
Section: In Vitro and In Vivo Biocompatibility Of The Pga Composite H...mentioning
confidence: 99%